Financial hardships and psychosocial outcomes among parents of children who die of cancer. Issue 2 (13th December 2022) - Davis, Elizabeth S.; Wimberly, Courtney E.; Towry, Lisa; Johnston, Emily E.; Walsh, Kyle M.
Abstract: Background: Caregivers experience financial hardship during a child's cancer treatment and after their child's death. These bereaved caregivers also experience negative psychosocial outcomes following the death of a child, but the relationship between financial hardship and negative psychosocial outcomes is poorly understood in this population. Methods: We surveyed self‐selected bereaved caregivers as part of a publicly posted survey through Alex's Lemonade Stand Foundation in order to explore family experiences after losing a child to cancer. The survey contained questions regarding parent psychosocial and financial outcomes following their child's death. Results: One‐hundred seventy‐six caregivers completed the survey a median of 7 years after their child's death. The majority were female (91%), non‐Hispanic White (97%), and married or living with a domestic partner (76%). Overall, 31% of caregivers reported that their child's death significantly impacted the financial well‐being of their family, 23% experienced a decrease in income following their child's death, and 14% were still paying medical expenses. Financial hardship that the caregiver attributed to the child's death was associated with feeling lonely and isolated (adjusted relative risk [ARR] = 1.7, 95% CI: 1.1–2.7) and living day to day (ARR = 1.8, 95% CI: 1.3–2.5), even after adjustment for household income and time since child's death. Conclusions: Caregivers experience multiple financial hardships following the death of a child to cancer, which endure for years after the child's death. These hardships are associated with negative psychosocial outcomes, demonstrating the need for both financial and psychosocial interventions for caregivers following the death of a child to cancer.